Development of secondary sexual characters in the seabob shrimp Xiphopenaeus kroyeri (Heller 1862) (Crustacea, Decapoda, Penaeidae): a scanning electron microscope study - Fransozo, Vivian [UNESP]; dos Santos, Daniela Carvalho [UNESP]; Lopez-Greco, Laura Suzana; Bolla Junior, Eduardo Antonio [UNESP] (Int Science Services/balaban Publishers, 2011)
The development of secondary sexual characters, the petasma, and thelycum growth were studied in Xiphopenaeus kroyeri. In adult females, the thelycum is a single plate and its anterolateral portion is characterized by a reduced hood. The aperture resembles a transverse ridge. In immature stages, the ridge has a space between the plates, which becomes narrower as it reaches the end of development. The female gonopore is 'comma' shaped. In adult males, the endopods of the petasma are linked at the dorsomedial margin by a large quantity of cincinnuli. In juveniles, cincinnuli gradually increase in number until they join both endopods. At the end of development the petasma is T-shaped. The male gonopore is C-shaped. The relative growth of the petasma total length versus juvenile body length showed a highly positive allometry, whereas in adults the growth was isometric. For the relationship carapace length versus thelycum width, the juvenile phase of females is characterized by an isometry and the adult phase by a negative allometry.
Keywords: external morphology; secondary sexual characters; seabob shrimp; sexual dimorphism; ultrastructure; allometric growth